Analisis Yuridis Penetapan Alasan Pembelaan Terpaksa Berdasarkan Surat Tap-209/M.6.10/Eoh.1/12/2023: Di Kejaksaan Negeri Serang - Fikri Dwi Fadillah; Iron Fajrul Aslami; Safiulloh Safiulloh (Lembaga Pengembangan Kinerja Dosen, 2024)
In the case of a man who killed a goat thief in Serang, Banten, namely the case of Muhyani (58), the prosecutor issued a Letter of Decision to Terminate Prosecution with the Number Tap-209/M.6.10/Eoh.1/12/2023, in which there was an identification of the problem of society still not understanding the Criminal Code regulations regarding the Reasons for Forgiveness in the elimination of criminal acts, so this research aims to 1. Understand the legal perspective on forced defense according to Article 49 paragraph 1 of the Criminal Code, 2. Know the resolution in a case of forced defense (Noodweer) then in the research, namely 1) How is the study of the form of reasons for forgiveness in criminal law in Indonesia?, 2) What are the considerations in determining the existence of reasons for forgiveness in the case of letter Tap-209/M.6.10/Eoh.1/12/2023 in the prosecutor's office and police investigation. In this thesis, the normative legal research method is used through the approach of legislation, cases, and conceptual approaches. then connected with related laws, then analyzed using legal theory, and conducting interviews. Article 49 paragraph (1) of the Criminal Code stipulates that,